The Effect Nanocapsule of Turmeric Extracts in Rations on Nutrient Digestibility of Broiler Chickens - Sundari, Sundari; Zuprizal, Zuprizal; Yuwanta, T; Martien, R (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. The use of turmeric is restricted by its low solubility in water, therefore it has low bioavailability. This obstacle can be solved by the development of nanoparticle technology to improve drug delivery profile. This study aimed to develop nanoparticle formulation using turmeric extract and industrial chitosan as the matrix and sodium-tripolyphosphate as cross linker, to study its ability to improve feed digestibility. Method used in the formulation of nanoparticle in this study was by ionic gelation followed by oven drying at 50°C. Method used to evaluate the digestibility was total collection. One hundred and twenty broiler chickens with an average body weight of 900 g, were randomly divided into 20 treatments (one treatment was fasted and 19 were treated with the ration plus feed additive), and six replicates were performed on each test. Chickens were fasted one day before and after they were treated with rations. Nutrient levels and the amount of feed consumed and excreta released were weighed to calculate the digestibility of the ration. It was found that the basal ration had dry matter digestibility of 70.48% significantly lower compared to the basal ration plus nanocapsule turmeric extract: NP level at 0.4% for in EE and EA were 73.11 and 75.90%. The results of this study concluded that formulation of nanocapsule using turmeric extract and industrial chitosan as the matrix and sodium tripolyphosphate as cross linker was potential to increase nutrient digestibility, therefore, it can be an alternative for feed additive in broiler chicken diet. Key words: Digestibility, nanocapsule, turmeric extract, broiler chicken Abstrak. Penggunaan kunyit/kurkumin terbatas karena kelarutannya yang rendah dalam air sehingga bioavailabilitasnya juga rendah. Masalah ini dapat diatasi dengan teknologi nano yang dikembangkan sebagai alternatif penghantaran obat bagi bahan kimia yang mempunyai bioavailabilitas rendah. Penelitian ini bertujuan untuk mengembangkan formulasi nanokapsul menggunakan ekstrak kunyit dan kitosan industri sebagai matrik atau polimer serta sodium tripolifosfat sebagai cross linker, untuk dipelajari kemampuannya dalam meningkatkan kecernaan ransum. Metode yang digunakan dalam formulasi nanokapsul adalah gelasi ionik dilanjutkan pengeringan dengan oven pada suhu 50°C. Sedangkan metode untuk mengevaluasi kecernaan menggunakan total koleksi. Seratus dua puluh ekor ayam broiler dengan bobot badan rata-rata 900 g, dibagi secara acak ke dalam 20 perlakuan (satu perlakuan dipuasakan dan 19 diberi ransum perlakuan dengan penambahan feed additive), masing-masing enam ulangan dan satu ekor untuk tiap ulangan. Ayam dipuasakan sehari pada sebelum dan sesudah ayam diperlakukan dengan ransum, kadar nutrien dan jumlah pakan yang dikonsumsi serta ekskreta yang dikeluarkan ditimbang beratnya untuk menghitung kecernaan ransum. Telah ditemukan bahwa kecernaan bahan kering ransum basal (70,48%) nyata lebih kecil dibanding ransum basal yang ditambah nanokapsul ekstrak kunyit: pada NP level 0,4% sebesar 73,11% pada EE dan 75,90% pada EA. Dapat disimpulkan bahwa formulasi nanokapsul menggunakan ekstrak kunyit dan kitosan industri sebagai matrik dan sodiumtripolifosfat sebagai cross-linker berpotensi sebagai feed additive alternatif untuk meningkatkan kecernaan nutrien pada ransum ayam broiler. Kata kunci: Kecernaan, nanokapsul, ekstrak kunyit, ayam broiler